2020
DOI: 10.5194/hess-24-3157-2020
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of weather radar in heavy rain: a comparative study for Denmark, the Netherlands, Finland and Sweden

Abstract: Abstract. Weather radar has become an invaluable tool for monitoring rainfall and studying its link to hydrological response. However, when it comes to accurately measuring small-scale rainfall extremes responsible for urban flooding, many challenges remain. The most important of them is that radar tends to underestimate rainfall compared to gauges. The hope is that by measuring at higher resolutions and making use of dual-polarization radar, these mismatches can be reduced. Each country has developed its own … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 101 publications
5
33
1
Order By: Relevance
“…Only about 0.3 percentage points of the MAP underestimation can be attributed to the radar gaps due to the reduced radius, so that there is quite a systematic negative bias in the data. Most other studies on radar-based QPE evaluations also revealed underestimations of precipitation totals [9,[53][54][55][56], but a few authors reported an overestimation [54,57]. However, such results are hard to compare due to large differences in radar hardware, correction algorithms and evaluation methods in the studies.…”
Section: Discussionmentioning
confidence: 93%
“…Only about 0.3 percentage points of the MAP underestimation can be attributed to the radar gaps due to the reduced radius, so that there is quite a systematic negative bias in the data. Most other studies on radar-based QPE evaluations also revealed underestimations of precipitation totals [9,[53][54][55][56], but a few authors reported an overestimation [54,57]. However, such results are hard to compare due to large differences in radar hardware, correction algorithms and evaluation methods in the studies.…”
Section: Discussionmentioning
confidence: 93%
“…Of course, the method is also sensitive to uncertainties hidden in radar data. The authors in [95] showed that radar precipitation estimates tend to underestimate intensive precipitation based on the evaluation of specific events in the territory of four different states. In the case of the proposed method, this means that it will underestimate the flash flooding hazard.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to account for this spatial variability with geostatistical techniques (e.g., ordinary kriging, kriging with external drift or co-kriging; Krajewski, 1987;Creutin et al, 1988;Wackernagel, 2003;Schuurmans et al, 2007;Goudenhoofdt and Delobbe, 2009;Sideris et al, 2014) or Bayesian merging methods (Todini, 2001). Although these methods substantially improve the QPE in the spatial domain, all gauge-based radar QPE adjustment methods are limited by the timely availability of sufficient, and ideally qualitycontrolled, rain gauge observations (for an overview of methods and their limitations, see Ochoa-Rodriguez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%